Effect of Mechanized Pedestrian Overpass to Reduce Accidents and Improve the Safety of vulnerable Pedestrians (Case Study: Esfahan) - Mohsen i Aboutalebi Esfahan; Alireza Afshari (توسعه پایدار شهری)
Walking in public spaces is one of the sustainable transport achievement pillars. High amount of driving accident fatalities, which are related to pedestrians specially children and elderlies, emphasis on the importance of vulnerable pedestrian safety. So, pedestrian overpass are constructed to enhance the user physical safety and protect the interface of vehicles and pedestrians. The aim of this research is to study the relationship between amount of vulnerable pedestrians’ accidents, time and age of injuries, in addition, the effect of mechanized pedestrian overpass on decreasing the passersby accidents. This article has compiled Isfahan pedestrian accidents statistics between 1391 to 1395 in two age groups of children and the elderlies and derived bridge crossing model according to age with using field studies and logistic regression method. The results showed that the rate of pedestrian accidents are correlated with age and time of the accidents. It seems that mechanization can help to increase the pedestrian bridges usage. Users who are more than 64 years old with an average of 76/8% had the most welcoming of automatic bridges but still 30.2% of people are not agree with this viewpoint. Speed of passing vehicles and the limiting fences under overpasses are effective factors for using pedestrian bridges. Also accessibility to elevator next to the pedestrian bridges can be helped to pass on more easily.